The exponential era : strategies to thrive in an era of chaotic changes and disruptive forces - Espindola, David; Wright, Michael W. (Hoboken, New Jersey : Wiley-IEEE Press, 2021)
"This book introduces the concept of an Exponential Era, a time when change within the business world occurs at a rate too steep for business managers to keep track of and react. The book is organized in three sections. In Section I the authors provide context for the realities of the Exponential Era, driven in particular by the growth of computing capacity. The book then describes the confluence of several high-value technology platforms such as Artificial Intelligence, Blockchain, Internet of Things, Biotechnology and others. Section II is about how organizations can deal effectively with the realities of the Exponential Era by following a robust methodology the authors call SPX that challenges the current thinking in strategic planning. Section III discusses the impact of the Exponential Era on humanity, and how the rapid changes we are experiencing challenges our current societal structures, economics, and ethics."--
The New Context for Our Future -- Exponential Platforms -- Animals of the Exponential Kingdom -- Introducing SPX -- Detecting Early Signals -- Learning from Experiments -- Capabilities -- The Essential Fuel to Ride the Exponential Curve -- Feedback-Based Strategic Decisions -- Leading a Culture of Change -- The Exponential Human -- Social and Ethical Challenges in a Chaotic World.
Includes index.
Description based on online resource; title from digital title page (viewed on November 09, 2021).
John Wiley and Sons
Keywords: Business; Business enterprises -- Technological innovations; Affaires; Entreprises -- Innovations; businesses (business enterprises); business (commercial function); Business; Business enterprises -- Technological innovations